AJTE 2017
DOI: 10.14221/ajte.2017v42n2.6
|View full text |Cite
|
Sign up to set email alerts
|

Children with Speech Sound Disorders at School: Challenges for Children, Parents and Teachers

Abstract: Teachers play a major role in supporting children 's educational, social, and emotional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
16
1
3
Order By: Relevance
“…Valuing the individuality of clients might be driven by SLPs' knowledge of the social impacts of having an SSD. These include an increased risk of bullying; poor peer relationships; less enjoyment for school (McCormack et al, 2011); feelings of frustration, embarrassment, and sadness about having an SSD (Daniel & McLeod, 2017); and feelings of isolation and confusion as the result of frequent communication breakdowns (Markham et al, 2009). While SLPs in this study prioritized clients' values, perspectives, and circumstances as one of the three elements of EBP, they demonstrated opinions and insight about evidence of therapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…Valuing the individuality of clients might be driven by SLPs' knowledge of the social impacts of having an SSD. These include an increased risk of bullying; poor peer relationships; less enjoyment for school (McCormack et al, 2011); feelings of frustration, embarrassment, and sadness about having an SSD (Daniel & McLeod, 2017); and feelings of isolation and confusion as the result of frequent communication breakdowns (Markham et al, 2009). While SLPs in this study prioritized clients' values, perspectives, and circumstances as one of the three elements of EBP, they demonstrated opinions and insight about evidence of therapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…While most children are ready for verbal communication at preschool age, some lack speech and linguistic abilities equal to their peers [1]. Such abilities can limit the children’s inclusion in the social and educational environment [2]. Due to this, speech and linguistic abilities play an important role in human society and are crucial for establishing verbal communication.…”
Section: Introductionmentioning
confidence: 99%
“…As for people's perception of alterations in speech, in Q18 (parents) the most frequent answer was "speech" and the associations were "speak, exchanges, delay, took, place, follow-up, relatives, motivate and different", showing that other people as well observe the aspects related to the functioning of speech in children, many of the times in a derogatory way. In a study carried out in Australia 25 , parents reported that, in public spaces, they had to protect their children in response to other people's reaction to the children's speech, mainly in regard to social aspects and emotional issues.…”
Section: Discussionmentioning
confidence: 99%